Borrowing Smarter or Borrowing More? Investigating the Effects of a Change in Federal Loan Policy. (6th June 2020) - Lee, Jason C.; Ciarimboli, Erin B.; Rubin, Paul G.; González Canché, Manuel S.
ABSTRACT: Much of the student loan literature focuses on institutional, individual, and family- level characteristics associated with indebtedness, default, and other undesirable post-graduation outcomes; however, relatively little research examines the role that federal policy has played in student borrowing. This study addresses this gap by analyzing the effects of a change in Stafford loan limits that impacted one subgroup of borrowers. Findings consistently revealed that increases in federal loan limits did not result in students borrowing more. Instead, students utilized newly available Stafford loan dollars to substitute away from other loan sources with less favorable terms, such as private and parent PLUS loans.